The Nitrogen Cycle at Regional to Global Scales - Boyer, Elizabeth W.; Howarth, Robert W. (Springer Netherlands, 2002)
This issue is the final report from the International SCOPE Project on Nitrogen Transport and Transformations: A Regional and Global Analysis. SCOPE (the Scientific Committee on Problems of the Environment, ICSU) authorized the Nitrogen Project as an 8-year effort between 1994 and 2002 because of the need to better understand how humans have altered nitrogen cyc1ing globally and at the scale of large regions. Human activity has more than doubled the rate of formation of reactive nitrogen on the land surface of the earth, and the nitrogen cyc1e continues to accelerate. The distribution of this reactive nitrogen is not uniform, though, and some regions such as Europe and Asia have seen massive increases in reactive nitrogen, while other regions have seen little change. The SCOPE Nitrogen Project has synthesized detailed information on the nature of the human alteration of the nitrogen cyc1e through aseries of workshops over the past 8 years. These cumulatively have involved over 250 of previous workshops scientists from over 20 different nations. The results have been published in aseries of special journal issues and reports that synthesize information on nitrogen in the North Atlantic Ocean and its water sheds (Howarth 1996), nitrogen cycling in Asia (Hong-Chi Lin et al. 1996; Mosier et al
Keywords: Biochemistry, general; Biochemistry; Stickstoffkreislauf; Biogeochemie; Aufsatzsammlung; Konferenzschrift